2022
DOI: 10.1101/2022.06.03.494762
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calcitonin Gene-Related Peptide (CGRP) Receptor Antagonism Reduces Motion Sickness Indicators in Mouse Migraine Models

Abstract: Migraine and vestibular migraine (VM) are associated with enhanced motion sensitivity, and VM is the most common cause of spontaneous vertigo but remains poorly understood. It is now accepted that migraine involves the neuropeptide Calcitonin Gene-Related Peptide (CGRP); yet it is not clear if CGRP signaling or its antagonism is involved in motion sensitivity of VM symptoms. Recent murine models of migraine used injections of CGRP or other migraine triggers (sodium nitroprusside SNP) to induce migraine sens… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 55 publications
(98 reference statements)
2
6
0
Order By: Relevance
“…Our findings in a further two mouse strains are consistent with that study and another recent murine motion sickness study (Rahman & Luebke, 2022). In young adult C57BL/6 and transgenic ChAT-gCaMP6 f mice, we found similar T tail responses, although ChAT-gCaMP6 f mice showed an elevated peak T tail compared to C57BL/6 mice within 6-7 min of PM onset (Figure 4a).…”
Section: Motion Sickness In Rodents and Pm-induced Thermal Responsesupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings in a further two mouse strains are consistent with that study and another recent murine motion sickness study (Rahman & Luebke, 2022). In young adult C57BL/6 and transgenic ChAT-gCaMP6 f mice, we found similar T tail responses, although ChAT-gCaMP6 f mice showed an elevated peak T tail compared to C57BL/6 mice within 6-7 min of PM onset (Figure 4a).…”
Section: Motion Sickness In Rodents and Pm-induced Thermal Responsesupporting
confidence: 92%
“…While sexual dimorphism is of interest, it was not an aim of this study to compare male and female mice since we only had access to males in the aged group. By chance, we had a predominantly female representation in young adult cohorts, but we suggest it should not influence our agedependent results significantly since Rahman and Luebke (2022) show there were no differences in PM response between young adult males and females.…”
Section: Effects Of Aging On the Susceptibility Of Motion Sicknessmentioning
confidence: 84%
See 1 more Smart Citation
“…In the nausea/dizziness assay after provocative motion there is a decrease in head temperature and an increase in tail temperature. We have shown that in wildtype C57BL/6J mice injection of CGRP prolongs the head temperature response and blunts the transient tail temperature increase, whereas a CGRP-receptor antagonist can reverse these CGRP-induced changes (21,27,28). Therefore, we investigated if a MA10-SARS-CoV-2 viral infection would show similar acute dizziness/nausea responses as CGRP injection, and if antagonizing CGRP signaling could reduce these dizziness/nausea responses and/or other signs of SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 95%
“…We used MA10-SARS-CoV-2 to assess both neurological symptoms of fever and dizziness/nausea in mouse models after infection. As a readout of the nausea-like state present after SARS-CoV-2 infection, we examined hypothermic responses to provocative motion, as we have previously used to assess migraine nausea pain (21) and others have used to assess motion-sensitivity in transgenic mouse models (22). Studies have demonstrated that provocative motion causes robust and prominent hypothermic responses in rats, humans, house musk shrews, and mice.…”
Section: Introductionmentioning
confidence: 99%